PENGARUH HARGA DISKON DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN JASA OJEK ONLINE GOJEK DI KOTA SURABAYA - Kukuh Wahyu Widjayanto; Siti Maroah; Muhammad Alhakim Danurwindo (PROCEEDING UMSURABAYA, 2022)
During the COVID-19 pandemic, online drivers GOJEK complains that the number of orders for their service has decreased significantly. It becomes common issue that their income becomes less and less during this pandemic. The reason of the decrease can be because people are reluctant to use public transportation, so they choose to use private vehicles. Another reason is that there are many activities carried out from home such as work from home (WFH) and learning from home.The purpose of this research is to determine and analyze the effect of discounted prices and brand image on the decision to purchase online taxi services GOJEK in the city of Surabaya. The research was conducted using a quantitative approach with data collection techniques using a questionnaire. The research sample is Gojek users who used the services at least twice on GoRide and GoCar services numbering 100 respondents. The data analysis technique was done by using multiple linear regression analysis.Â The results showed that discounted prices had a significant positive effect on purchasing decisions, brand image, and on purchasing decisions. Moreover, discounted prices and brand image had a significant positive effect on purchasing decisions for online taxi services Gojek.Keywords: Discounted Price; Brand Image; Service Purchase Decision